Experimental investigation of galinstan based minichannel cooling for high heat flux and large heat power thermal management. (1st April 2019) - Zhang, Xu-Dong; Yang, Xiao-Hu; Zhou, Yi-Xin; Rao, Wei; Gao, Jian-Ye; Ding, Yu-Jie; Shu, Qing-Qing; Liu, Jing
Highlights: A practical galinstan based minichannel cooling system was developed, which can dissipate heat 300 W/cm 2 and 1500 W. The thermal performance and hydrodynamic characteristic of galinstan based minichannel heat sink was evaluated. The heat capacity thermal resistance was an important factor for galinstan based minichannel cooling. The pressure losses of galinstan minichannel heat sink was far lower than the water microchannel heat sink. This cooling system can operate silently, steadily and smoothly. Abstract: This paper is dedicated to experimentally investigate the liquid galinstan based minichannel cooling for high heat flux and large heat power thermal management. Firstly, a compact electromagnetic pump towards effectively driving liquid metals was developed, which can provide high pressure head up to 100 kPa. Then, the minichannel heat sink was designed and manufactured, with width of channel 1 mm, height of channel 5 mm. Furthermore, the galinstan based minichannel cooling system was established and experimentally tested under different heating loads and pumping powers. The results show that galinstan based minichannel cooling system can dissipate heat with heat flux 300 W/cm 2 and heat power 1500 W. And the thermal performance and hydrodynamic characteristic of minichannel heat sink using galinstan as coolant were obtained. It indicates that compared to water based minichannel cooling, galinstan based minichannel cooling can obtain a rather larger heat transfer enhancement, and the pressure losses of galistan based minichannel heat sink is much lower than that of water based microchannel cooling. Moreover, it is also found that heat capacity thermal resistance becomes a rather important factor for the thermal performance of galinstan based minichannel, due to the high thermal conductivity and lower heat capacity of galinstan. Furthermore, the galinstan based minichannel cooling system can operate silently, steadily and smoothly by using electromagnetic pump, which has no moving parts. Overall, the galinstan based minichannel cooling is proven to be a powerful and practical way for the thermal management of high heat flux and large heat power devices.